2017
DOI: 10.1038/eye.2017.79
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence rate of retinal detachment after small gauge vitrectomy for idiopathic epiretinal membrane

Abstract: PurposeTo assess the occurrence rate of retinal detachment (RD) after small gauge vitrectomy for idiopathic epiretinal membrane (ERM).Patients and methodsRetrospective observational case series. The records of consecutive patients operated on for idiopathic ERM using small gauge pars plana vitrectomy between August 2012 and December 2014 with at least a 1-year follow-up were reviewed. All patients were contacted by phone to assess the occurrence of RD during the post-operative follow-up. The main outcome was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
0
9
2
Order By: Relevance
“…Detailed examination of the periphery with indentation before the finalization of the surgery may reveal retinal breaks during the surgery. One of the crucial complications of vitrectomy is the iatrogenic peripheral retinal tears which usually occur while inducing the posterior hyaloid detachment or performing peripheral vitreous shaving and should to be treated with laser photocoagulation promptly [14], [15], [16], [17]. In this study peripheral vitreous shaving with or without scleral indentation techniques were not performed in any cases, and no iatrogenic retinal tears were detected with this technique.…”
Section: Discussionmentioning
confidence: 79%
“…Detailed examination of the periphery with indentation before the finalization of the surgery may reveal retinal breaks during the surgery. One of the crucial complications of vitrectomy is the iatrogenic peripheral retinal tears which usually occur while inducing the posterior hyaloid detachment or performing peripheral vitreous shaving and should to be treated with laser photocoagulation promptly [14], [15], [16], [17]. In this study peripheral vitreous shaving with or without scleral indentation techniques were not performed in any cases, and no iatrogenic retinal tears were detected with this technique.…”
Section: Discussionmentioning
confidence: 79%
“…Only 2 eyes of 212 eyes had postoperative retinal detachment. The authors concluded that small gauge sutureless vitrectomy improved the safety of ERM surgery (7).…”
Section: Discussionmentioning
confidence: 98%
“…Recent advances in vitreoretinal surgery have made ERM membrane surgery a very safe procedure [3, 10]. Together with the fact that in almost all reports, preoperative visual acuity is the main prognostic factor of postoperative visual acuity [2, 11, 12], this is leading to surgery being proposed to patients with very good visual acuities.…”
Section: Discussionmentioning
confidence: 99%